La falta de concursos de mérito y oposición en el sector público del Ecuador - Paredes Paladines, Alisson Katherine (2025)
This scientific article focuses on the effects of the lack of merit-based competitive exams for permanent appointments in Ecuador’s public sector. This issue affects the principles of equality, efficiency, and transparency within public institutions. By reviewing the legal framework of the Organic Law of Public Service (LOSEP) and its regulations, all relevant legal provisions were analyzed. The general objective is to examine the effects of the absence of competitive exams for permanent positions in Ecuador’s public sector. A qualitative research approach was applied, as its goal was to collect all the necessary and relevant information detailed in bibliographic references. Three research methods were used: the analytical-synthetic method, the legal hermeneutic method, and the inductive-deductive method. Each of these was significant in the study. The results were obtained through interviews and surveys conducted with professionals in the field, whose responses provided insights into the lack of competitive exams and the job instability it generates. In conclusion, the study highlights the importance of analyzing the effects and consequences of the absence of merit-based selection processes in the public sector to develop measures that can help improve the system.